Catalyst for catalyzing CO as well as preparation method and application of catalyst
A catalyst for CO oxidation is prepared by treating glass fiber with acid to form a microporous structure and applying coatings, enhancing surface area and bonding, thus improving CO removal efficiency and resistance to water and sulfur.
Patent Information
- Application Number
- CN202411277648.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-17
AI Technical Summary
Existing CO catalysts are not suitable for catalytic oxidation due to poor sulfur resistance and efficiency at medium temperatures, and they do not provide adequate water resistance.
A catalyst preparation method involving a glass fiber corrugated plate treated with acid to create a controllable three-dimensional microporous structure, combined with a transition and diffusion coating to enhance surface area and bonding, reducing active component use and improving thermal shock resistance.
The catalyst achieves high CO removal efficiency under medium temperatures with improved water and sulfur resistance, ensuring effective catalytic performance and durability.
Smart Images

Figure CN119140118A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst for catalyzing CO and a preparation method and application thereof. Background Art
[0002] CO is a common source of air pollution. It is highly toxic to the blood and nervous system of the body. Even a small amount of CO inhalation can cause damage to the body. There are two main methods for eliminating CO: physical elimination and chemical elimination. Among the chemical elimination methods, catalytic oxidation is considered to be one of the most efficient methods because of its low operating temperature and environmental friendliness.
[0003] CN110681398A discloses a noble metal catalyst for purifying carbon dioxide gas, comprising 60-95% of a carrier, 0.01-1% of an active component, 2-35% of an active aid, and 2-15% of a molding aid. The carrier is one or more of alumina, silicon dioxide, and molecular sieves, and the active component is one or more of Pd and Pt oxides. The active aid is one or more of Fe, Mn, Cu, Ni, Co, Ce, Zr, and La oxides. The molding aid is one or more of sesbania powder, kaolin, attapulgite, glass fiber powder, and high-alumina cement. The catalyst is not suitable for catalytic oxidation of carbon monoxide.
[0004] CN116237060A discloses a method for preparing a wide-temperature sulfur-resistant CO oxidation catalyst, comprising the following steps: step 1, preparing a 3-6 mol / L HNO3 solution, adding distilled water to dilute it, dispersing pseudo-boehmite powder in the mixed solution, and refluxing and stirring to obtain a γ-AlOOH sol; step 2, weighing and filtering a metal element precursor and anhydrous sodium carbonate, placing them in a mortar and grinding them to obtain a viscous solid, adding the viscous solid to the γ-AlOOH sol, refluxing and stirring, and adding 1-3 mol / L sodium carbonate solution during the reaction to adjust the pH value to 8-10; step 3, filtering the reaction solution while hot, and washing it with distilled water, drying and grinding the obtained solid in an oven, and then calcining it in a 10-30% O2 / Ar atmosphere to obtain MO x -Al2O3 carrier; Step 4, mixing the ethylene glycol solution of the Pt precursor and the ethylene glycol solution of the alkali metal hydroxide, and heating them in an argon atmosphere to obtain a brown-black Pt glue; MO x -Al2O3 carrier is added to Pt glue, PVP aqueous solution is added, magnetic stirring is carried out at room temperature, acetic acid is added dropwise to adjust pH=4-6, and after heating in a water bath, the obtained solid is filtered and washed, and the obtained solid is dried to obtain a catalyst semi-finished product; the catalyst semi-finished product is placed in a 10-30% O2 / Ar atmosphere and calcined to obtain a catalyst finished product. The sulfur resistance of the catalyst is poor.
[0005] CN118105992A discloses a hydrothermal and sulfur-resistant CO oxidation integral catalyst, comprising powder A, powder B and a binder. Powder A comprises a carrier, an active component and an additive. The carrier of powder A is alumina composite oxide A (M1N1O x -Al2O3), where M1O x 、N1O x The active component of powder A is one or more of silicon oxide, lanthanum oxide, nickel oxide, barium oxide, magnesium oxide, zirconium oxide or calcium oxide. The active component of powder A is one or more of Pt, Pd and Ru. Powder B includes a carrier, an active component and an additive. The carrier of powder B is a titanium oxide-based composite oxide M2N2O x -TiO2, where M2O x 、N2O x The active component of powder B is one or more of Pt and Ru. The auxiliary agent is one or more of lanthanum oxide, tin oxide, calcium oxide, copper oxide, potassium oxide, sodium oxide or magnesium oxide. The sulfur resistance of the catalyst needs to be improved. Summary of the invention
[0006] In view of this, an object of the present invention is to provide a method for preparing a catalyst for catalyzing CO, wherein the glass fiber corrugated plate is treated with acid to obtain a controllable three-dimensional microporous structure and a large specific surface area, and the pore size of the carrier is controlled between 8 and 14 nm; the catalyst obtained by the preparation method has a high removal efficiency for CO under medium temperature conditions. Furthermore, the CO catalyst obtained by the preparation method has good water and sulfur resistance.
[0007] The preparation of transition coating can not only improve the roughness of glass fiber surface, increase the specific surface area of catalyst, but also improve the macroporous structure; moreover, the coating is firmly bonded to the carrier surface, which is beneficial to the thermal shock resistance of catalyst, and is also beneficial to the loading and dispersion of precious metals and other active components, thereby reducing the amount of active components and improving the catalytic performance.
[0008] The above purpose is achieved through the following technical solutions.
[0009] In one aspect, the present invention provides a method for preparing a catalyst for catalyzing CO, comprising the following steps:
[0010] (1) reacting a water-soluble inorganic aluminum salt, aluminum powder and water at 70 to 100° C., then adding an inorganic acid to adjust the pH to 2 to 4; adding polyethylene glycol and stirring for 1 to 5 hours to obtain a transition coating slurry;
[0011] (2) immersing the glass fiber corrugated plate carrier into the transition coating slurry to obtain a carrier loaded with the transition coating slurry; drying the carrier loaded with the transition coating slurry, and then calcining to obtain an intermediate;
[0012] (3) mixing Cu, polyethylene glycol, Pt, silica sol and water, and ball milling to obtain a diffusion coating slurry; wherein the mass ratio of Cu, polyethylene glycol, Pt and silica sol is (5-12): (5-12): (0.05-0.4): (2-8);
[0013] (4) pouring the diffusion coating slurry onto the intermediate, and then blowing off the excess slurry on the intermediate to obtain the intermediate loaded with the diffusion coating slurry; drying the intermediate loaded with the diffusion coating slurry, and then calcining to obtain the catalyst.
[0014] According to the preparation method of the present invention, preferably, the water-soluble inorganic aluminum salt is selected from one or more of aluminum chloride, aluminum sulfate, and aluminum nitrate, and the inorganic acid is selected from one or more of hydrochloric acid, nitric acid, and sulfuric acid.
[0015] According to the preparation method of the present invention, preferably, the mass ratio of the water-soluble inorganic aluminum salt to the aluminum powder is (1-4):1.
[0016] According to the preparation method of the present invention, preferably, the particle size of the solid particles in the diffusion plating slurry is 1 to 50 μm.
[0017] According to the preparation method of the present invention, preferably, the silica sol is acidic silica sol.
[0018] According to the preparation method of the present invention, preferably, in step (2), the glass fiber corrugated board carrier is immersed in the transition coating slurry for 30 to 90 minutes, the drying temperature is 100 to 130°C, the roasting temperature is 400 to 600°C, and the roasting time is 3 to 8 hours.
[0019] According to the preparation method of the present invention, preferably, in step (4), the drying temperature is 100-130° C., the roasting temperature is 400-600° C., and the roasting time is 3-8 h.
[0020] In another aspect, the present invention provides a catalyst for catalyzing CO, wherein the catalyst is obtained by the above preparation method.
[0021] In still another aspect, the present invention provides use of the above catalyst in catalytic oxidation of carbon monoxide.
[0022] According to the use of the present invention, preferably, the carbon monoxide exists in a gaseous substance, the concentration of the carbon monoxide is 1000-20000 ppm, and the operating temperature of the catalyst is 200-280°C.
[0023] The transition coating of the catalyst of the present invention can improve the roughness of the surface of the glass fiber corrugated plate carrier, increase the specific surface area of the catalyst, control the pore size of the carrier to 8-14nm, and improve the macroporous structure. The transition coating is firmly combined with the carrier surface, which is conducive to the uniform loading of the diffusion coating, reduces the amount of active components, improves the catalytic performance, and is conducive to the thermal shock resistance of the catalyst. The carrier, transition coating and diffusion coating of the present invention cooperate with each other to improve the removal efficiency of the catalyst for CO under medium temperature conditions and improve the water and sulfur resistance of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a diagram of the pore structure of the glass fiber corrugated plate catalyst. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0026] <Method for preparing catalyst>
[0027] The preparation method of the catalyst for catalyzing CO of the present invention comprises the following steps:
[0028] (1) a step of preparing a transition coating slurry; (2) a step of obtaining an intermediate; (3) a step of preparing a diffusion plating slurry; and (4) a step of obtaining a catalyst.
[0029] Steps for preparing the transition coating slurry
[0030] The invention reacts water-soluble inorganic aluminum salt, aluminum powder and water at 70-100° C., then adds inorganic acid to adjust the pH to 2-4; adds polyethylene glycol and stirs for 1-5 hours to obtain transition coating slurry.
[0031] The water-soluble inorganic aluminum salt can be selected from one or more of aluminum chloride, aluminum sulfate, and aluminum nitrate. According to one embodiment of the present invention, the inorganic aluminum salt is aluminum chloride. The inorganic aluminum salt can be used in the form of its hydrate, for example, AlCl3·6H2O.
[0032] The mass ratio of the water-soluble inorganic aluminum salt to the aluminum powder is (1-4):1; preferably (2-3.5):1; more preferably (2-3):1.
[0033] The mass ratio of water to aluminum powder may be (2-10):1; preferably (2.5-6):1; more preferably (3-5):1.
[0034] The reaction temperature of the water-soluble inorganic aluminum salt, aluminum powder and water is 70 to 100°C, preferably 80 to 95°C, and more preferably 85 to 90°C.
[0035] The inorganic acid can be selected from one or more of hydrochloric acid, nitric acid and sulfuric acid. According to one embodiment of the present invention, the inorganic acid is nitric acid. The mixture of water-soluble inorganic aluminum salt, aluminum powder and water can be adjusted to 2-4 with nitric acid; preferably 2.5-3.
[0036] After adding polyethylene glycol, stir for 1 to 5 hours, preferably 2 to 3 hours.
[0037] The amount of polyethylene glycol used is 10-20wt% of the total mass of the water-soluble inorganic aluminum salt, aluminum powder and water; preferably 12-18wt%; more preferably 12-15wt%.
[0038] Such a transition coating slurry can improve the removal efficiency of the catalyst for CO under medium temperature conditions and improve the water and sulfur resistance of the catalyst.
[0039] Steps to obtain intermediates
[0040] The present invention immerses a glass fiber corrugated plate carrier into transition coating slurry to obtain a carrier loaded with transition coating slurry; dries the carrier loaded with transition coating slurry, and then roasts it to obtain an intermediate.
[0041] The immersion time in the transition coating slurry can be 30 to 90 minutes, preferably 40 to 70 minutes, and more preferably 50 to 60 minutes. After the immersion, the excess slurry in the three-dimensional micropores of the glass fiber corrugated board carrier can be blown out. Specifically, compressed air can be used to blow out the excess slurry in the three-dimensional micropores of the glass fiber corrugated board carrier. In this way, a suitable transition coating can be formed on the surface of the glass fiber corrugated board carrier.
[0042] The drying temperature may be 100-130°C; preferably 110-120°C.
[0043] The calcination temperature may be 400 to 600°C, preferably 450 to 550°C, and more preferably 500 to 550°C.
[0044] The calcination time may be 3 to 8 hours, preferably 4 to 7 hours, and more preferably 5 to 6 hours.
[0045] In some embodiments, the method further comprises the following steps: immersing the glass fiber corrugated plate in an acidic solution, washing it with water until it is neutral, and then drying it to obtain a glass fiber corrugated plate carrier. In this way, a controllable three-dimensional microporous structure and a large specific surface area can be obtained.
[0046] The acidic solution can be selected from one or more of an acetic acid aqueous solution, a nitric acid aqueous solution, and a citric acid aqueous solution. Preferably, the acidic solution is a citric acid aqueous solution. The concentration of the citric acid aqueous solution can be 5 to 20 wt %, preferably 8 to 15 wt %, and more preferably 10 to 12 wt %.
[0047] The drying temperature may be 100-130° C., preferably 110-120° C. The drying may be carried out in an oven.
[0048] The use of AlCl3·6H2O, aluminum powder and polyethylene glycol to prepare the transition coating can improve the roughness of the glass fiber surface, which is conducive to the firm bonding of the coating and the carrier surface, and is also beneficial to the loading and dispersion of precious metals and other active components, reducing the amount of active components and improving catalytic performance. In addition, the specific surface area of the catalyst is increased, a controllable three-dimensional microporous structure is obtained, and the sulfur resistance and water resistance are improved.
[0049] Steps for preparing diffusion plating slurry
[0050] Cu, polyethylene glycol, Pt, silica sol and water are mixed and ball milled to obtain a diffusion coating slurry.
[0051] The molecular weight of polyethylene glycol may be 1500 to 3000, preferably 1800 to 2500, and more preferably 2000 to 2200.
[0052] The mass ratio of Cu to polyethylene glycol can be (5-12): (5-12); preferably (6-10): (6-10); more preferably (9-10): (9-10). This helps to improve the removal efficiency of CO by the catalyst and improve the water and sulfur resistance of the catalyst.
[0053] The mass ratio of Cu to Pt can be (5-12):(0.05-0.4); preferably (6-10):(0.06-0.3); more preferably (9-10):(0.1-0.15). This helps to improve the catalyst's CO removal efficiency and improve the catalyst's water and sulfur resistance.
[0054] The silica sol may be an acidic silica sol, and the pH of the acidic silica sol may be 2.2 to 3.6.
[0055] The mass ratio of Cu to silica sol can be (5-12): (2-8); preferably (6-10): (3-6); more preferably (9-10): (4-5). This helps to improve the catalyst's CO removal efficiency and improve the catalyst's water and sulfur resistance.
[0056] The amount of water used may be equal to the volume of the fiberglass corrugated board carrier.
[0057] The particle size of the solid particles in the diffusion plating slurry can be 1 to 50 μm, preferably 5 to 20 μm.
[0058] Steps to obtain the catalyst
[0059] The present invention pours diffusion coating slurry onto the intermediate, then blows off the excess slurry on the intermediate to obtain the intermediate loaded with diffusion coating slurry; dries the intermediate loaded with diffusion coating slurry, then roasts to obtain the catalyst.
[0060] The drying temperature may be 100-130°C; preferably 110-120°C.
[0061] The calcination temperature may be 400-600° C., preferably 450-550° C., and more preferably 500-550° C. The calcination time may be 3-8 hours, preferably 4-7 hours, and more preferably 5-6 hours. The calcination may be performed in a muffle furnace.
[0062] <Catalyst and its use>
[0063] The catalyst for catalyzing CO of the present invention is obtained by the above preparation method. The catalyst of the present invention has a high removal efficiency for CO and has excellent water and sulfur resistance. Therefore, the present invention provides the use of the above catalyst in catalytic oxidation of carbon monoxide.
[0064] Carbon monoxide may be present in the gaseous substance. The gaseous substance may also contain SO2 and H2O. In certain embodiments, the gaseous substance may also contain NO and CO2.
[0065] The concentration of carbon monoxide in the gaseous substance may be 1000 to 20000 ppm, preferably 5000 to 15000 ppm, and more preferably 5000 to 10000 ppm.
[0066] The SO2 content may be 50 to 200 ppm; preferably 80 to 150 ppm; more preferably 100 to 120 ppm.
[0067] The content of H2O may be 8 to 20 vol%, preferably 10 to 17 vol%, and more preferably 13 to 15 vol%.
[0068] The content of NO may be 100 to 500 ppm; preferably 200 to 400 ppm; more preferably 300 to 350 ppm.
[0069] The content of CO2 may be 5 to 25 vol%, preferably 10 to 20 vol%, and more preferably 10 to 15 vol%.
[0070] The catalyst can be used at a temperature of 200 to 280°C, preferably 240 to 270°C.
[0071] The airspeed can be 15000~25000h -1 ; preferably 18000~23000h -1More preferably, 20000 to 21000 hours -1 .
[0072] Here is the test method:
[0073] The catalyst was placed in a quartz reaction tube for CO activity test. The space velocity was 20000h -1 The reaction gas composition is CO 5000ppm, NO 300ppm, SO2 100ppm, CO2 10vol%, H2O 13vol%.
[0074] Example 1
[0075] The glass fiber corrugated board was immersed in a citric acid solution with a concentration of 10 wt %, taken out, washed with water until neutral, and then dried in an oven at 110° C. to obtain a glass fiber corrugated board carrier.
[0076] AlCl3·6H2O and aluminum powder in a mass ratio of 2:1 were mixed with water, heated and stirred at 90°C until the aluminum powder was completely reacted, and then nitric acid was added to adjust the pH to 3, and polyethylene glycol was added and stirred for 3 hours to obtain a transition coating slurry. The mass ratio of water to aluminum powder was 2.5:1, and the amount of polyethylene glycol was 12wt% of the total mass of AlCl3·6H2O, aluminum powder and water.
[0077] The glass fiber corrugated plate carrier is immersed in the transition coating slurry, taken out after immersion for 60 minutes, and then the excess slurry in the three-dimensional micropores of the glass fiber corrugated plate carrier is blown out with compressed air to obtain a carrier loaded with the transition coating slurry. The carrier loaded with the transition coating slurry is dried at 110°C, and then calcined in a muffle furnace at 500°C for 5 hours to obtain an intermediate.
[0078] Cu, polyethylene glycol 2000, Pt and acidic silica sol (pH 2.2-3.6) were mixed in a mass ratio of 10:10:0.1:5, and then deionized water was added and ball milled to obtain a diffusion coating slurry with a particle size of 5-20 μm. The amount of deionized water used was equal to the volume of the glass fiber corrugated board carrier.
[0079] The diffusion coating slurry is poured onto the intermediate, and then the excess slurry on the intermediate is blown off with compressed air to obtain the intermediate loaded with the diffusion coating slurry. The intermediate loaded with the diffusion coating slurry is dried at 110°C, and then calcined in a muffle furnace at 500°C for 5 hours to obtain a catalyst.
[0080] The catalyst of this embodiment can achieve a CO removal efficiency of 98% at 250°C; after 24 hours of testing, the CO removal efficiency of the catalyst at 250°C is always above 95%.
[0081] Example 2
[0082] The glass fiber corrugated board was immersed in a citric acid solution with a concentration of 10 wt %, taken out, washed with water until neutral, and then dried in an oven at 110° C. to obtain a glass fiber corrugated board carrier.
[0083] AlCl3·6H2O and aluminum powder in a mass ratio of 3:1 were mixed with water, heated and stirred at 90°C until the aluminum powder was completely reacted, and then nitric acid was added to adjust the pH to 3, and polyethylene glycol was added and stirred for 3 hours to obtain a transition coating slurry. The mass ratio of water to aluminum powder was 3:1, and the amount of polyethylene glycol was 15wt% of the total mass of AlCl3·6H2O, aluminum powder and water.
[0084] The glass fiber corrugated plate carrier is immersed in the transition coating slurry, taken out after immersion for 60 minutes, and then the excess slurry in the three-dimensional micropores of the glass fiber corrugated plate carrier is blown out with compressed air to obtain a carrier loaded with the transition coating slurry. The carrier loaded with the transition coating slurry is dried at 110°C, and then calcined in a muffle furnace at 500°C for 5 hours to obtain an intermediate.
[0085] Cu, polyethylene glycol 2000, Pt and acidic silica sol (pH 2.2-3.6) were mixed in a mass ratio of 8:8:0.15:3, and then deionized water was added and ball milled to obtain a diffusion coating slurry with a particle size of 5-20 μm. The amount of deionized water used was equal to the volume of the glass fiber corrugated board carrier.
[0086] The diffusion coating slurry is poured onto the intermediate, and then the excess slurry on the intermediate is blown off with compressed air to obtain the intermediate loaded with the diffusion coating slurry. The intermediate loaded with the diffusion coating slurry is dried at 110°C, and then calcined in a muffle furnace at 500°C for 5 hours to obtain a catalyst.
[0087] The catalyst of this embodiment can achieve a CO removal efficiency of 96% at 250°C; after 24 hours of testing, the CO removal efficiency of the catalyst at 250°C is always above 95%.
[0088] Example 3
[0089] The glass fiber corrugated board was immersed in a citric acid solution with a concentration of 10 wt %, taken out, washed with water until neutral, and then dried in an oven at 110° C. to obtain a glass fiber corrugated board carrier.
[0090] AlCl3·6H2O and aluminum powder in a mass ratio of 2:1 were mixed with water, heated and stirred at 90°C until the aluminum powder was completely reacted, and then nitric acid was added to adjust the pH to 2.5, and polyethylene glycol was added and stirred for 3 hours to obtain a transition coating slurry. The mass ratio of water to aluminum powder was 2.5:1, and the amount of polyethylene glycol was 15wt% of the total mass of AlCl3·6H2O, aluminum powder and water.
[0091] The glass fiber corrugated plate carrier is immersed in the transition coating slurry, taken out after immersion for 60 minutes, and then the excess slurry in the three-dimensional micropores of the glass fiber corrugated plate carrier is blown out with compressed air to obtain a carrier loaded with the transition coating slurry. The carrier loaded with the transition coating slurry is dried at 110°C, and then calcined in a muffle furnace at 500°C for 5 hours to obtain an intermediate.
[0092] Cu, polyethylene glycol 2000, Pt and acidic silica sol (pH 2.2-3.6) were mixed in a mass ratio of 9:9:0.08:4, and then deionized water was added and ball milled to obtain a diffusion coating slurry with a particle size of 5-20 μm. The amount of deionized water used was equal to the volume of the glass fiber corrugated board carrier.
[0093] The diffusion coating slurry is poured onto the intermediate, and then the excess slurry on the intermediate is blown off with compressed air to obtain the intermediate loaded with the diffusion coating slurry. The intermediate loaded with the diffusion coating slurry is dried at 110°C, and then calcined in a muffle furnace at 500°C for 5 hours to obtain a catalyst.
[0094] The catalyst of this embodiment can achieve a CO removal efficiency of 96% at 250°C; after 24 hours of testing, the CO removal efficiency of the catalyst at 250°C is always above 95%.
[0095] Example 4
[0096] The glass fiber corrugated board was immersed in a citric acid solution with a concentration of 10 wt %, taken out, washed with water until neutral, and then dried in an oven at 110° C. to obtain a glass fiber corrugated board carrier.
[0097] AlCl3·6H2O and aluminum powder in a mass ratio of 3:1 were mixed with water, heated and stirred at 90°C until the aluminum powder was completely reacted, and then nitric acid was added to adjust the pH to 2.5, and polyethylene glycol was added and stirred for 3 hours to obtain a transition coating slurry. The mass ratio of water to aluminum powder was 3:1, and the amount of polyethylene glycol was 12wt% of the total mass of AlCl3·6H2O, aluminum powder and water.
[0098] The glass fiber corrugated plate carrier is immersed in the transition coating slurry, taken out after immersion for 60 minutes, and then the excess slurry in the three-dimensional micropores of the glass fiber corrugated plate carrier is blown out with compressed air to obtain a carrier loaded with the transition coating slurry. The carrier loaded with the transition coating slurry is dried at 110°C, and then calcined in a muffle furnace at 500°C for 5 hours to obtain an intermediate.
[0099] Cu, polyethylene glycol 2000, Pt and acidic silica sol (pH 2.2-3.6) were mixed in a mass ratio of 7:7:0.2:6, and then deionized water was added and ball milled to obtain a diffusion coating slurry with a particle size of 5-20 μm. The amount of deionized water used was equal to the volume of the glass fiber corrugated board carrier.
[0100] The diffusion coating slurry is poured onto the intermediate, and then the excess slurry on the intermediate is blown off with compressed air to obtain the intermediate loaded with the diffusion coating slurry. The intermediate loaded with the diffusion coating slurry is dried at 110°C, and then calcined in a muffle furnace at 500°C for 5 hours to obtain a catalyst.
[0101] The catalyst of this embodiment can achieve a CO removal efficiency of 95% at 250°C; after 24 hours of testing, the CO removal efficiency of the catalyst at 250°C is always above 95%.
[0102] Example 5
[0103] The glass fiber corrugated board was immersed in a citric acid solution with a concentration of 10 wt %, taken out, washed with water until neutral, and then dried in an oven at 110° C. to obtain a glass fiber corrugated board carrier.
[0104] AlCl3·6H2O and aluminum powder in a mass ratio of 2:1 were mixed with water, heated and stirred at 90°C until the aluminum powder was completely reacted, and then nitric acid was added to adjust the pH to 2.5, and polyethylene glycol was added and stirred for 3 hours to obtain a transition coating slurry. The mass ratio of water to aluminum powder was 3.5:1, and the amount of polyethylene glycol was 12wt% of the total mass of AlCl3·6H2O, aluminum powder and water.
[0105] The glass fiber corrugated plate carrier is immersed in the transition coating slurry, taken out after immersion for 60 minutes, and then the excess slurry in the three-dimensional micropores of the glass fiber corrugated plate carrier is blown out with compressed air to obtain a carrier loaded with the transition coating slurry. The carrier loaded with the transition coating slurry is dried at 110°C, and then calcined in a muffle furnace at 500°C for 5 hours to obtain an intermediate.
[0106] Cu, polyethylene glycol 2000, Pt and acidic silica sol (pH 2.2-3.6) were mixed in a mass ratio of 9.8:9.8:0.08:4.5, and then deionized water was added and ball milled to obtain a diffusion coating slurry with a particle size of 5-20 μm. The amount of deionized water used was equal to the volume of the glass fiber corrugated board carrier.
[0107] The diffusion coating slurry is poured onto the intermediate, and then the excess slurry on the intermediate is blown off with compressed air to obtain the intermediate loaded with the diffusion coating slurry. The intermediate loaded with the diffusion coating slurry is dried at 110°C, and then calcined in a muffle furnace at 500°C for 5 hours to obtain a catalyst.
[0108] The catalyst of this embodiment can achieve a CO removal efficiency of 97% at 250°C; after 24 hours of testing, the CO removal efficiency of the catalyst at 250°C is always above 95%.
[0109] Table 1
[0110]
[0111] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A method for preparing a catalyst for catalyzing CO, It is characterized in that The steps include: (1) reacting a water-soluble inorganic aluminum salt, aluminum powder and water at 70 to 100° C., then adding an inorganic acid to adjust the pH to 2 to 4; adding polyethylene glycol and stirring for 1 to 5 hours to obtain a transition coating slurry; (2) immersing the glass fiber corrugated plate carrier into the transition coating slurry to obtain a carrier loaded with the transition coating slurry; drying the carrier loaded with the transition coating slurry, and then calcining to obtain an intermediate; (3) mixing Cu, polyethylene glycol, Pt, silica sol and water, and ball milling to obtain a diffusion coating slurry; wherein the mass ratio of Cu, polyethylene glycol, Pt and silica sol is (5-12): (5-12): (0.05-0.4): (2-8); (4) pouring the diffusion coating slurry onto the intermediate, and then blowing off the excess slurry on the intermediate to obtain the intermediate loaded with the diffusion coating slurry; drying the intermediate loaded with the diffusion coating slurry, and then calcining to obtain the catalyst.
2. The preparation method according to claim 1, It is characterized in that The water-soluble inorganic aluminum salt is selected from one or more of aluminum chloride, aluminum sulfate, and aluminum nitrate, and the inorganic acid is selected from one or more of hydrochloric acid, nitric acid, and sulfuric acid.
3. The preparation method according to claim 1, It is characterized in that The mass ratio of water-soluble inorganic aluminum salt to aluminum powder is (1-4):
1.
4. The preparation method according to claim 1, It is characterized in that The particle size of the solid particles in the diffusion plating slurry is 1 to 50 μm.
5. The preparation method according to claim 1, It is characterized in that The silica sol is acidic silica sol.
6. The preparation method according to claim 1, It is characterized in that In step (2), the glass fiber corrugated board carrier is immersed in the transition coating slurry for 30 to 90 minutes, the drying temperature is 100 to 130° C., the roasting temperature is 400 to 600° C., and the roasting time is 3 to 8 hours.
7. The preparation method according to claim 1, It is characterized in that In step (4), the drying temperature is 100-130° C., the roasting temperature is 400-600° C., and the roasting time is 3-8 hours.
8. A catalyst for catalyzing CO, It is characterized in that The catalyst is obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the catalyst according to claim 8 in catalytic oxidation of carbon monoxide.
10. The use according to claim 9, It is characterized in that The carbon monoxide exists in gaseous substances, the concentration of the carbon monoxide is 1000-20000 ppm, and the operating temperature of the catalyst is 200-280°C.
